Intentional and unintentional benefits of minority writing accountability groups. Issue 11 (November 2022) - Spencer, Elsie C.; Neikirk, Kit; Campbell, Susan L.; Powell-Roach, Keesha L.; Morton, Derrick; Shuler, Haysetta; Murray, Sandra A.; Hinton, Antentor
Abstract : A faculty position can be a balancing act. Many new faculty, particularly minorities, struggle due to a lack of mentorship. Writing accountability groups (WAGs) offer new faculty an opportunity to glean advice from mentors and improve their writing skills and enhance their career development in science, technology, engineering, and mathematics (STEM).